Penerapan Uji Statistik Parametrik : Uji t dan Anova Dua Faktor Dalam Penelitian Kuantitatif - Yandrizal Chaniago; Anisa Kamila sari; Adiman; M. Imamuddin (JOSEE : Jurnal Intelektual Mahasiswa, 2026)
Quantitative research requires appropriate statistical analysis methods to ensure that research results are scientifically valid. One of the most commonly used statistical methods is parametric statistics, particularly the t-test and two-way ANOVA. This article aims to explain the concepts, functions, types, conditions, and applications of the t-test and two-way ANOVA in quantitative research. This study employs a literature review (library research) using a descriptive-analytical approach, drawing on various relevant books and scientific journals. The findings indicate that the t-test is used to determine differences in means between two groups, while two-way ANOVA is used to analyze the effects of two independent variables on a single dependent variable and to examine interactions between factors. Furthermore, if the ANOVA results indicate a significant difference, a post hoc test is required to identify which groups differ significantly. The appropriate use of parametric statistical tests can enhance the validity, objectivity, and quality of quantitative research results.